Efficient degradation PP composite material and preparation method thereof
A core-shell structured PP composite with modified starch and PLA filler addresses the challenge of balancing mechanical performance and degradation efficiency by leveraging PLA's rapid biodegradation and starch's nutritional role for microorganisms.
Patent Information
- Application Number
- CN202510538273.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-27
- Publication Date
- 2025-07-15
- Estimated Expiration
- 2045-04-27
AI Technical Summary
Existing PP materials are difficult to degrade in natural environments, and existing modification methods are difficult to achieve efficient degradation while maintaining mechanical properties.
Core-shell composite degradation filler is used to form a double-bridge agglomerator through the addition of γ-mercaptopropyltriethoxysilane and diallylamine, which is coupled to starch to form modified starch. The enrichment of stannous chloride on the surface of the starch promotes the ring-opening polymerization of L-lactide, forming a polylactic acid-covered starch structure. Combined with maleic anhydride grafted polypropylene as a compatibility agent, PP composites are blended and extruded.
It realizes efficient degradation of PP composite materials, improves the mechanical properties of the materials, especially tensile strength and impact toughness, and adjusts the degradation rate by controlling the PLA shell thickness and starch core particle size, adapting to different application scenarios.
Smart Images

Figure CN120310134A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer composite materials, and specifically relates to a highly degradable PP composite material and a preparation method thereof. Background Art
[0002] As a general-purpose thermoplastic, polypropylene (PP) is widely used in the fields of packaging, automobiles, household appliances, etc. due to its excellent mechanical properties, chemical resistance, and low cost. However, traditional PP materials are difficult to degrade in the natural environment.
[0003] To relieve environmental pressure, existing technologies mainly achieve composite modification by introducing degradable materials into the PP matrix, which can be specifically divided into two categories: one is to use natural materials such as starch and wood powder as fillers, which have the characteristics of rapid biodegradation themselves, but due to the poor compatibility between their hydrophilicity and the hydrophobicity of the PP matrix, the mechanical properties of the composite material are significantly reduced, restricting its application in mechanically sensitive scenarios; the other is to blend PP with degradable polymer materials such as polylactic acid and polycaprolactone. Such materials have good compatibility with PP and have little impact on mechanical properties, but their degradation rate is slow and it is difficult to meet the actual degradation requirements. Therefore, existing technologies generally face the core contradiction that it is difficult to synergistically optimize "degradation efficiency" and "material properties", and there is an urgent need for an innovative solution that can both maintain the mechanical properties of the PP matrix and achieve efficient degradation. Summary of the Invention
[0004] In order to solve the technical problems mentioned in the background art, the purpose of the present invention is to provide a highly degradable PP composite material and a preparation method thereof.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A highly degradable PP composite material, the components of which are: 39 - 46 wt% of core-shell composite degradation filler, 3.5 - 4.2 wt% of compatibilizer, 1.8 - 2.3 wt% of lubricant, 0.12 - 0.15 wt% of nucleating agent, and 0.08 - 0.1 wt% of antioxidant, with the balance being PP resin.
[0007] Among them, the core-shell composite degradation filler is prepared by the following method:
[0008] Step A1: Stir and mix diallylamine, γ-mercaptopropyltriethoxysilane, and anhydrous acetone in a dry atmosphere, irradiate with ultraviolet light of 300 - 400 mW / cm 2 and slowly add a photosensitizer to stir and react for 12 - 15 h at room temperature, and then evaporate acetone to obtain a double-bridge aggregating agent;
[0009] In the reaction of step A1 above, the feeding ratio of diallylamine, γ-mercaptopropyltriethoxysilane, photosensitizer and anhydrous acetone is 0.1 mol: 0.2 mol: 0.16 - 0.22 g: 350 - 400 mL. Under the initiation of ultraviolet irradiation, γ-mercaptopropyltriethoxysilane adds to diallylamine. The specific reaction route is as follows:
[0010]
[0011] Step A2: Premix the double-bridge aggregating agent, non-ionic emulsifier and tetrahydrofuran aqueous solution, adjust the pH value of the premixed solution to 3 - 4 with hydrochloric acid, add starch and disperse it by ultrasonic wave, then change to stirring at 120 - 150 rpm for 2 - 2.5 h, centrifuge to remove the supernatant, and spray-dry the bottom concentrated solution to obtain modified starch;
[0012] In the reaction of step A2 above, the feeding ratio of starch, double-bridge aggregating agent, non-ionic emulsifier and tetrahydrofuran aqueous solution is 50 g: 3.6 - 4.2 g: 1.1 - 1.5 g: 220 - 260 mL. The mass fraction of the tetrahydrofuran aqueous solution is 50 - 60%, and the terminal ethoxysilane structure of the double-bridge aggregating agent hydrolyzes and couples with starch to form starch cluster microparticles doped with the double-bridge aggregating agent.
[0013] Step A3: Premix the modified starch, stannous chloride, p-toluenesulfonic acid and dimethyl sulfoxide, then add the chloroform solution of L-lactide and mix well. Pass in nitrogen for protection, raise the temperature to 150 - 160 °C and stir for reaction for 6 - 7 h. Then reduce the pressure to 50 Pa, raise the temperature to 210 - 220 °C and continue the reaction for 3.5 - 4 h. Discharge, cool, wash and dry to obtain the core-shell composite degradable filler;
[0014] In the reaction of step A3 above, the feeding ratio of modified starch, L-lactide, stannous chloride, p-toluenesulfonic acid and dimethyl sulfoxide is 50 g: 8.5 - 11 g: 0.18 - 0.24 g: 0.1 - 0.13 g: 150 - 200 mL. The thioether and amino structures introduced by the double-bridge aggregating agent in the modified starch form a chelating effect, enriching stannous chloride on the surface of the modified starch, which promotes the initial ring-opening polymerization of L-lactide on the surface of the modified starch to form a composite structure with polylactic acid coating the starch.
[0015] Preferably, the compatibilizer is maleic anhydride grafted polypropylene, which plays a good compatibilizing role between the PP matrix and the polylactic acid shell layer of the core-shell composite degradable filler.
[0016] Preferably, the nucleating agent is an amide nucleating agent, which promotes the formation of β-phase crystallization in the PP matrix, facilitating the improvement of the overall strength and toughness of the composite material.
[0017] A preparation method of an efficient degradable PP composite material, specifically: premix PP resin, compatibilizer, lubricant, nucleating agent and antioxidant and feed them from the main feeding port of the extruder, and feed the core-shell composite degradable filler from the side feeding port of the extruder, and co-extrude to obtain the efficient degradable PP composite material.
[0018] Preferably, the barrel temperature zones of the extruder are set as follows: zone 1: 170 - 180 °C, zone 2: 180 - 190 °C, zone 3: 190 - 200 °C, zone 4: 200 - 210 °C, zone 5: 200 - 210 °C, zone 6: 200 - 210 °C, and the die head: 210 - 220 °C.
[0019] The beneficial effects of the present invention:
[0020] Through the design of the core-shell composite degradable filler and its specific preparation process, the present invention realizes the synergistic improvement of the degradation efficiency and mechanical properties of the PP composite material. The core-shell composite degradable filler is prepared by adding γ-mercaptopropyltriethoxysilane and diallylamine to form a double-bridge agglomerating agent with double-branched triethoxysilane, which hydrolyzes and couples with starch to form starch cluster microparticles doped with the double-bridge agglomerating agent, that is, modified starch. The sulfur ether and amino structures introduced by the double-bridge agglomerating agent in the modified starch form a chelating effect, and stannous chloride is enriched on the surface of the modified starch, which promotes the initial ring-opening polymerization of L-lactide on the surface of the modified starch to form a composite structure with poly(lactic acid) coating starch. Compared with the prior art, the shell layer of the core-shell composite degradable filler is poly(lactic acid) (PLA), and its compatibility with the PP matrix is better than that of natural starch, effectively alleviating the interfacial defect problem caused by traditional starch fillers and reducing the deterioration of key mechanical indexes such as the tensile strength and impact toughness of the composite material. After the PLA shell layer breaks, the microcracks formed extend to the PP matrix, increasing the specific surface area of the material and promoting the contact of PP chain segments with oxygen, moisture and microorganisms, breaking through the degradation inertia of traditional PP due to high crystallinity. Moreover, after the product is broken, the brittle PLA shell layer breaks first, exposing the internal starch core, and microorganisms rapidly reproduce using starch as a nutrient source, forming a local acidic microenvironment, accelerating the enzymatic hydrolysis and hydrolysis of the PLA shell layer. At the same time, the low molecular weight products generated by the degradation of PLA further stimulate the activity of microorganisms, forming a "starch-PLA-microorganism" synergistic degradation cycle, thus realizing deep and efficient degradation. In addition, by adjusting the thickness of the PLA shell layer and the particle size of the starch core, the balance between the degradation rate of the filler and the mechanical properties of the material can be customized to adapt to different application scenarios, which has far-reaching research significance. Description of the Drawings
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for the description of the embodiments will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.
[0022] Figure 1 This is the degradation rate curve of the granular specimens of Example 4 of the present invention and the comparative example.
[0023] Figure 2 This is the degradation rate curve of the sheet specimens of Example 4 of the present invention and the comparative example. Detailed implementation manners
[0024] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0025] Example 1, preparing a highly degradable PP composite material, specifically as follows:
[0026] (1) Preparation of core-shell composite degradation filler
[0027] Step A1: Take diallylamine, γ-mercaptopropyltriethoxysilane and anhydrous acetone, stir and mix them evenly in a dry atmosphere, irradiate with ultraviolet light of 300 mW / cm 2 , slowly add a photosensitizer and stir for reaction for 15 h at room temperature. Among them, the feeding ratio of diallylamine, γ-mercaptopropyltriethoxysilane, photosensitizer and anhydrous acetone is 0.1 mol: 0.2 mol: 0.16 g: 350 mL. The photosensitizer is selected as benzoin dimethyl ether (DMPA). Then, evaporate acetone to obtain a double-bridge aggregating agent.
[0028] Step A2: Take the double-bridge aggregating agent, non-ionic emulsifier and tetrahydrofuran aqueous solution for premixing, adjust the pH value of the premixed solution to 4 with hydrochloric acid, add starch and disperse it by ultrasonic wave, and then change to stirring at 120 rpm for 2.5 h. Among them, the feeding ratio of starch, double-bridge aggregating agent, non-ionic emulsifier and tetrahydrofuran aqueous solution is 50 g: 3.6 g: 1.1 g: 220 mL. The mass fraction of the tetrahydrofuran aqueous solution is 50%. The non-ionic emulsifier is selected as Tween 80. Centrifuge to remove the supernatant, and spray-dry the bottom concentrated solution to obtain modified starch.
[0029] Step A3: Take the modified starch, stannous chloride, p-toluenesulfonic acid and dimethyl sulfoxide for premixing, then add a chloroform solution of L-lactide and mix evenly, introduce nitrogen for protection, raise the temperature to 150 °C and stir for reaction for 7 h, then reduce the pressure to 50 Pa, raise the temperature to 210 °C and continue to react for 4 h. Among them, the feeding ratio of modified starch, L-lactide, stannous chloride, p-toluenesulfonic acid and dimethyl sulfoxide is 50 g: 8.5 g: 0.18 g: 0.1 g: 150 mL. Discharge, cool, wash and dry to obtain the core-shell composite degradation filler.
[0030] (2) Preparation of the composite material
[0031] Ingredients: 39 wt% of core-shell composite degradation filler, self-made in this example; 3.5 wt% of compatibilizer, PO 1020 type maleic anhydride grafted polypropylene is selected; 2.3 wt% of lubricant, 6108C type polypropylene wax is selected; 0.15 wt% of nucleating agent, BT-5 type amide nucleating agent is selected; 0.1 wt% of antioxidant, antioxidant 1010 and antioxidant 168 are used in a compound ratio of 2:1 by weight, and the balance is PP resin, and K1003 type resin raw material is selected.
[0032] Co-blending and molding: Premix PP resin, compatibilizer, lubricant, nucleating agent and antioxidant and feed them from the main feed port of the extruder, feed the core-shell composite degradation filler from the side feed port of the extruder, and control the temperature zones of the extruder barrel to be set as: zone 1 at 180 °C, zone 2 at 190 °C, zone 3 at 200 °C, zone 4 at 210 °C, zone 5 at 210 °C, zone 6 at 210 °C, and the die head at 220 °C. Co-extrude each component to obtain a highly degradable PP composite material.
[0033] Example 2, preparation of a highly degradable PP composite material, is as follows:
[0034] (1) Preparation of the core-shell composite degradation filler
[0035] Step A1: Take diallylamine, γ-mercaptopropyltriethoxysilane and anhydrous acetone, stir and mix them evenly in a dry atmosphere, irradiate with ultraviolet light at 400 mW / cm 2 and slowly add a photosensitizer and stir for reaction for 12 h at room temperature. Among them, the feeding ratio of diallylamine, γ-mercaptopropyltriethoxysilane, photosensitizer and anhydrous acetone is 0.1 mol: 0.2 mol: 0.22 g: 400 mL. The photosensitizer is selected as benzoin dimethyl ether, and then acetone is distilled off to obtain a double-bridge aggregating agent.
[0036] Step A2: Premix the double-bridge aggregating agent, non-ionic emulsifier and tetrahydrofuran aqueous solution, adjust the pH value of the premixed solution to 3 with hydrochloric acid, add starch and disperse it by ultrasonic wave, and then change to stirring at 150 rpm for 2 h. Among them, the feeding ratio of starch, double-bridge aggregating agent, non-ionic emulsifier and tetrahydrofuran aqueous solution is 50 g: 4.2 g: 1.5 g: 260 mL. The mass fraction of the tetrahydrofuran aqueous solution is 60%, the non-ionic emulsifier is selected as Tween 80, centrifuge to remove the supernatant, and spray-dry the bottom concentrated solution to obtain modified starch.
[0037] Step A3: pre-mix modified starch, stannous chloride, p-toluenesulfonic acid and dimethyl sulfoxide, add L-lactide dissolved in chloroform and mix well, introduce nitrogen protection, heat to 160°C and stir to react for 6 hours, then reduce the pressure to 50Pa, heat to 220°C and continue to react for 3.5 hours, wherein the feed ratio of modified starch, L-lactide, stannous chloride, p-toluenesulfonic acid and dimethyl sulfoxide is 50g:11g:0.24g:0.13g:200mL, cool the material, wash and dry to obtain a core-shell composite degradable filler.
[0038] (2) Preparation of composite materials
[0039] Ingredients: 46wt% of core-shell composite degradable filler, which is prepared in this embodiment; 4.2wt% of compatibilizer, which is PO 1020 maleic anhydride grafted polypropylene; 1.8wt% of lubricant, which is 6108C polypropylene wax; 0.12wt% of nucleating agent, which is BT-5 amide nucleating agent; 0.08wt% of antioxidant, which is antioxidant 1010 and antioxidant 168 compounded in a weight ratio of 2:1, and the remainder is PP resin, which is K1003 type resin raw material.
[0040] Blending molding: premix PP resin, compatibilizer, lubricant, nucleating agent and antioxidant and feed them from the main feeding port of the extruder, feed the core-shell composite degradable filler from the side feeding port of the extruder, control the extruder barrel temperature zone to be set as: zone 1 170°C, zone 2 180°C, zone 3 190°C, zone 4 200°C, zone 5 200°C, zone 6 200°C, die head 210°C, blend and extrude the components to obtain a high-efficiency degradable PP composite material.
[0041] Example 3, preparation of highly efficient degradable PP composite material, as follows:
[0042] (1) Preparation of core-shell composite degradable fillers
[0043] Step A1: Mix diallylamine, γ-mercaptopropyltriethoxysilane and anhydrous acetone in a dry atmosphere and stir until uniform. 2 Under ultraviolet irradiation, the photosensitizer was slowly added at room temperature and stirred for 14 hours, wherein the feed ratio of diallylamine, γ-mercaptopropyltriethoxysilane, photosensitizer and anhydrous acetone was 0.1 mol: 0.2 mol: 0.18 g: 380 mL, and benzoin dimethyl ether was selected as the photosensitizer. The acetone was then evaporated to obtain a double-bridge coagulation agent.
[0044] Step A2: premix a double-bridge coagulant, a non-ionic emulsifier and a tetrahydrofuran aqueous solution, adjust the pH value of the premixed solution to 3 with hydrochloric acid, add starch for ultrasonic dispersion, and then stir at 150 rpm for 2.2 hours, wherein the feed ratio of starch, double-bridge coagulant, non-ionic emulsifier and tetrahydrofuran aqueous solution is 50 g:3.9 g:1.3 g:240 mL, the mass fraction of the tetrahydrofuran aqueous solution is 50%, and Tween 80 is selected as the non-ionic emulsifier. The supernatant is removed by centrifugation, and the bottom concentrated solution is spray-dried to obtain modified starch.
[0045] Step A3: pre-mix modified starch, stannous chloride, p-toluenesulfonic acid and dimethyl sulfoxide, add L-lactide dissolved in chloroform and mix well, introduce nitrogen protection, heat to 160°C and stir to react for 6.2h, then reduce the pressure to 50Pa, heat to 210°C and continue to react for 4h, wherein the feed ratio of modified starch, L-lactide, stannous chloride, p-toluenesulfonic acid and dimethyl sulfoxide is 50g:10g:0.22g:0.1g:170mL, cool the material, wash and dry to obtain a core-shell composite degradable filler.
[0046] (2) Preparation of composite materials
[0047] Ingredients: 42wt% of core-shell composite degradable filler, which is prepared in this embodiment; 3.8wt% of compatibilizer, which is PO 1020 maleic anhydride grafted polypropylene; 2wt% of lubricant, which is 6108C polypropylene wax; 0.14wt% of nucleating agent, which is BT-5 amide nucleating agent; 0.09wt% of antioxidant, which is antioxidant 1010 and antioxidant 168 in a weight ratio of 2:1, and the remainder is PP resin, which is K1003 resin raw material.
[0048] Blending molding: premix PP resin, compatibilizer, lubricant, nucleating agent and antioxidant and feed them from the main feeding port of the extruder, feed the core-shell composite degradable filler from the side feeding port of the extruder, control the extruder barrel temperature zone to be set as: zone 1 180°C, zone 2 190°C, zone 3 200°C, zone 4 210°C, zone 5 210°C, zone 6 210°C, die head 220°C, blend and extrude the components to obtain a high-efficiency degradable PP composite material.
[0049] Example 4, preparation of a highly efficient degradable PP composite material, as follows:
[0050] (1) Preparation of core-shell composite degradable fillers
[0051] Step A1: Mix diallylamine, γ-mercaptopropyltriethoxysilane and anhydrous acetone in a dry atmosphere and stir until uniform. 2Ultraviolet irradiation, slowly add a photosensitizer at room temperature and stir for reaction for 13 h. Among them, the feeding ratio of diallylamine, γ-mercaptopropyltriethoxysilane, the photosensitizer and anhydrous acetone is 0.1 mol: 0.2 mol: 0.2 g: 350 mL. The photosensitizer is selected as benzoin dimethyl ether. Then, evaporate acetone to obtain a double-bridge aggregating agent.
[0052] Step A2: Premix the double-bridge aggregating agent, a non-ionic emulsifier and an aqueous tetrahydrofuran solution, adjust the pH value of the premixed solution to 3 with hydrochloric acid, add starch and disperse it by ultrasonic wave, and then change to stirring at 150 rpm for 2 h. Among them, the feeding ratio of starch, the double-bridge aggregating agent, the non-ionic emulsifier and the aqueous tetrahydrofuran solution is 50 g: 4.2 g: 1.3 g: 250 mL. The mass fraction of the aqueous tetrahydrofuran solution is 60%. The non-ionic emulsifier is selected as Tween 80. Centrifuge to remove the supernatant, and spray-dry the bottom concentrated solution to obtain modified starch.
[0053] Step A3: Premix the modified starch, stannous chloride, p-toluenesulfonic acid and dimethyl sulfoxide, then add a chloroform solution of L-lactide and mix well. Pass in nitrogen for protection, raise the temperature to 155 °C and stir for reaction for 7 h. Then, reduce the pressure to 50 Pa and raise the temperature to 210 °C and continue the reaction for 4 h. Among them, the feeding ratio of the modified starch, L-lactide, stannous chloride, p-toluenesulfonic acid and dimethyl sulfoxide is 50 g: 9.5 g: 0.22 g: 0.12 g: 180 mL. Discharge, cool, wash and dry to obtain a core-shell composite degradable filler.
[0054] (2) Preparation of the composite material
[0055] Ingredient preparation: 44 wt% of the core-shell composite degradable filler, which is self-made in this example; 4 wt% of a compatibilizer, selected as maleic anhydride grafted polypropylene of type PO 1020; 1.9 wt% of a lubricant, selected as polypropylene wax of type 6108C; 0.13 wt% of a nucleating agent, selected as an amide nucleating agent of type BT-5; 0.09 wt% of an antioxidant, selected as a compound of antioxidant 1010 and antioxidant 168 used in a weight ratio of 2:1. The balance is PP resin, selected as resin raw material of type K1003.
[0056] Co-blending and molding: Premix PP resin, the compatibilizer, the lubricant, the nucleating agent and the antioxidant and feed them from the main feeding port of the extruder, feed the core-shell composite degradable filler from the side feeding port of the extruder, control the temperature zones of the extruder barrel to be set as: zone 1 180 °C, zone 2 180 °C, zone 3 190 °C, zone 4 200 °C, zone 5 200 °C, zone 6 210 °C, die head 220 °C, co-blend and extrude each component to obtain a highly degradable PP composite material.
[0057] For the comparative example, referring to Example 4, replace the core-shell composite degradable filler with 40 wt% starch and 4 wt% polylactic acid micropowder, and the rest of the implementation process is exactly the same.
[0058] Samples were taken from the composite materials prepared as above, and tensile property tests were carried out in accordance with the standard of GB / T 1040.2-2018, and impact property tests were carried out in accordance with the standard of GB / T 1843-2008; the specific test results are shown in Table 1 as follows:
[0059] Table 1
[0060] Tensile strength / MPa Elongation at break / % <![CDATA[Impact strength / kJ·m -2 > Example 1 20.55 81.46 9.24 Example 2 17.14 89.53 11.65 Example 3 19.09 84.27 10.82 Example 4 18.31 86.50 10.57 Comparative example 11.63 52.86 8.03
[0061] It can be seen from the test data in Table 1 that the PP composite materials prepared in the examples have excellent strength and toughness, and the mechanical properties are significantly improved compared with those directly obtained from the starch and polylactic acid blend materials.
[0062] Sheet specimens with a specification of 100×50×10 mm were prepared from the above composite materials, and were crushed into granular specimens passing through a 2-mm sieve by a crusher. The soil burial degradation tests were carried out respectively with the humus soil in the same garden, and the degradation rate was characterized by calculating the weight loss rate by the weighing method, as Figure 1 - Figure 2 shown as the degradation rate curves of Example 4 and the comparative example;
[0063] From Figure 1 - Figure 2 the test results, it can be seen that the degradation rate of the sheet specimens of the PP composite material in Example 4 lags behind, and the degradation rate at 180 days is relatively low; the degradation rate of the crushed particles is significantly improved, which is similar to that of the comparative example, and the degradation rate at 180 days exceeds that of the comparative example, showing the characteristics of deep and efficient degradation.
[0064] In the description of the specification, the descriptions referring to the terms "one embodiment", "example", "specific example", etc. mean that the specific features, structures, materials or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in a suitable manner in any one or more embodiments or examples.
[0065] The above content is only an example and illustration of the concept of the present invention. Those skilled in the art of this technology can make various modifications or supplements to the described specific embodiments or use similar methods to replace them, as long as they do not deviate from the concept of the invention or exceed the scope defined by this claim book, they should all belong to the protection scope of the present invention.
Claims
1. An efficient PP composite material for degradation, characterized in that, The specific components are as follows: 39-46 wt% of core-shell composite degradable filler, 3.5-4.2 wt% of compatibilizer, 1.8-2.3 wt% of lubricant, 0.12-0.15 wt% of nucleating agent and 0.08-0.1 wt% of antioxidant, and the balance is PP resin; The core-shell composite degradable filler is prepared by the following method: Step A1: Stir and mix diallylamine, γ-mercaptopropyltriethoxysilane and anhydrous acetone under a dry atmosphere, and irradiate with ultraviolet light at 300-400 mW / cm 2 Slowly add a photosensitizer and stir for reaction for 12-15 h at room temperature, and then evaporate acetone to obtain a double-bridge aggregating agent; Step A2: Premix a double-bridge aggregating agent, a nonionic emulsifier and an aqueous solution of tetrahydrofuran, adjust the pH value of the premixed solution to 3-4 with hydrochloric acid, add starch and disperse it by ultrasonic wave, then change to stirring at 120-150 rpm for 2-2.5 h, centrifuge to remove the supernatant, and spray-dry the bottom concentrated solution to obtain modified starch; Step A3: Premix the modified starch, stannous chloride, p-toluenesulfonic acid and dimethyl sulfoxide, then add a chloroform solution of L-lactide and mix well, introduce nitrogen for protection, raise the temperature to 150-160 °C and stir for reaction for 6-7 h, then reduce the pressure to 50 Pa, raise the temperature to 210-220 °C and continue the reaction for 3.5-4 h, discharge, cool, wash and dry to obtain the core-shell composite degradable filler.
2. The high-efficiency degradable PP composite material according to claim 1, wherein The feeding ratio of diallylamine, γ-mercaptopropyltriethoxysilane, photosensitizer and anhydrous acetone is 0.1 mol: 0.2 mol: 0.16-0.22 g: 350-400 mL.
3. An efficient PP composite material for degradation according to claim 2, characterized in that, The feeding ratio of starch, double-bridge aggregating agent, nonionic emulsifier and aqueous solution of tetrahydrofuran is 50 g: 3.6-4.2 g: 1.1-1.5 g: 220-260 mL.
4. An efficient PP composite material for degradation according to claim 3, characterized in that The feeding ratio of modified starch, L-lactide, stannous chloride, p-toluenesulfonic acid and dimethyl sulfoxide is 50 g: 8.5-11 g: 0.18-0.24 g: 0.1-0.13 g: 150-200 mL.
5. An efficient PP composite material according to claim 1, characterized in that, The compatibilizer is maleic anhydride grafted polypropylene.
6. The highly efficient PP composite material for degradation according to claim 1, wherein The nucleating agent is an amide nucleating agent.
7. A preparation method of an efficient PP composite material for degradation according to any one of claims 1-6, characterized in that, Specifically: Premix PP resin, compatibilizer, lubricant, nucleating agent and antioxidant and feed them from the main feed port of the extruder, feed the core-shell composite degradable filler from the side feed port of the extruder, and co-extrude to obtain a highly degradable PP composite material.
8. The preparation method of an efficient PP composite material degradation according to claim 7, characterized in that, The barrel temperature zones of the extruder are set as follows: zone 1 is 170-180 °C, zone 2 is 180-190 °C, zone 3 is 190-200 °C, zone 4 is 200-210 °C, zone 5 is 200-210 °C, zone 6 is 200-210 °C, and the die head is 210-220 °C.
Citation Information
Patent Citations
Polypropylene / polylactic acid / starch composite material and preparation method thereof
CN103131150A
Production process of environment-friendly degradable plastic particles
CN118307885A
A biodegradable starch-based master batch and a method for preparing the same
WO2006066478A1
Dispersible and biodegradable modified starch additive for reinforced polymers
WO2023069403A1